The Law of Guarantee Engagement in Business Transactions in Indonesia - NAELIL AGUSTIN; NAJMAR RIZQIYATIL HASANAH (IJED: International Journal of Economy Development Research, 2025)
The law of collateral obligations is a crucial aspect in business transactions because it functions as a legal protection mechanism for creditors against the risk of default by debtors. This study aims to examine how the law of collateral obligations is applied in business practices and to examine the problems faced by the parties in the obligation relationship. This study uses a qualitative approach with a literature study method and in-depth interviews with legal practitioners and business actors. The results of the study show that although collateral instruments such as pawns, fiduciaries, mortgages, and mortgages have been legally regulated, their implementation in the field often faces obstacles, both in terms of legal understanding, contractual interpretation, and implementation of collateral execution. This study recommends the need to improve legal understanding among business actors and strengthen institutions in enforcing collateral law in order to create certainty and justice in business transactions.